THE EFFECT OF FINANCIAL RATIO AND BUSINESS RISK ON FIRM VALUE - Kumala, Tirta; Chandra, Santoso (E-Jurnal Akuntansi TSM, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of financial ratios and business risk on firm value. There are eight independent variables in this study, namely profitability, leverage, liquidity, business risk, company size, institutional ownership, asset management, and company growth. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022 with specifications for the energy industry, consumer cyclicals, and consumer non-cyclicals. The sampling technique used in this study is purposive sampling and uses multiple regressions in analyzing data. There are 58 companies that passed the sample selection criteria from 174 data. The results of this research indicate that profitability, leverage, business risk, and firm size affect firm value. Meanwhile, other independent variables such as liquidity, institutional ownership, assets management, and company growth have no effect on firm value.